Analisis Minat Belajar IPS Di SD/MI Melalui Metode Pembelajaran Interaktif Di Kurikulum Merdeka - Nova Dwi Rahmayanti; Alma Pratiwi Husain (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
Social Studies (IPS) learning in elementary schools (SD/MI) still faces low student learning interest due to conventional methods that emphasize memorization without linking material to real-life contexts. This study aims to examine the role and effectiveness of interactive learning methods and their alignment with the Merdeka Curriculum. The method used is a literature study with content analysis of journals, books, proceedings, and official documents published between 2020 and 2025. The results indicate that interactive media, such as visual materials developed using Canva, contextual simulations of market trading activities, and game-based evaluations through Quizizz, significantly increase student participation and enthusiasm. This approach is consistent with student-centered learning, differentiated instruction, conceptual understanding, critical thinking skills, and the development of the Pancasila Student Profile. The main challenges include limited technological facilities, teachers’ digital competence, and effective classroom management. Therefore, collaboration among the government, schools, and educators is necessary to ensure the optimal and equitable implementation of interactive learning in Social Studies across Indonesia.  Pembelajaran IPS di SD/MI masih menghadapi rendahnya minat belajar akibat metode konvensional yang menekankan hafalan tanpa keterkaitan dengan kehidupan nyata. Penelitian ini bertujuan mengkaji peran dan efektivitas metode pembelajaran interaktif serta kesesuaiannya dengan Kurikulum Merdeka. Metode yang digunakan ialah studi pustaka dengan analisis konten terhadap jurnal, buku, prosiding, dan dokumen resmi tahun 2020–2025. Hasil kajian menunjukkan bahwa media interaktif, seperti materi visual berbasis Canva, simulasi kontekstual kegiatan jual beli, dan evaluasi permainan melalui Quizizz, meningkatkan partisipasi dan antusiasme siswa. Pendekatan ini sejalan dengan pembelajaran berpusat pada siswa, diferensiasi, penguatan konsep, berpikir kritis, dan Profil Pelajar Pancasila. Tantangan utama meliputi keterbatasan sarana teknologi, kompetensi guru, dan pengelolaan kelas. Diperlukan kolaborasi pemerintah, sekolah, dan pendidik agar implementasi pembelajaran interaktif berjalan optimal dan merata di seluruh Indonesia nasional.